A comprehensive framework for decoding salty taste information from electroencephalography signals: distinguishing brain reactions to saltiness of comparable intensity - Jingjing Liu; Yifei Xu; Xingwang Lian; Tianming Liu; Haohao Ning; Xi Jiang; Shixin Yu; Shikun Liu; Lu Huang; Xiaojun Sun; Jiangyong Li; Dongfu Xu (Food Science and Human Wellness)
The perception of salty taste is crucial for individuals to make healthy food choices. Yet, the brain electrophysiological signals underlying salty taste perception have been poorly described. In this study, electroencephalography (EEG) was used to record brain activity induced by NaCl solution as a salty taste stimulus. A combination of a custom delivery device and stimulation paradigm was employed to preserve the salty taste signal clearly. A stimulus-response capture method was proposed that could adapt to individual differences in brain responses to salty taste and accurately segment salty taste response signals. Applying this method to the EEG processing workflow can form a complete data processing framework. The results showed that the neural response induced by salty taste reached a high activity level in the initial stage within a short period (0.2 s), and there was a sustained periodic response within 0.75 s after the stimulation. Moreover, the salty taste information in the EEG signal was decoded, and discrimination of 2 similar concentrations of salty taste solutions was achieved far above the chance level (average identification rate: 89.66%). This study demonstrated experimental paradigms and research methods for understanding salty taste perception, which could provide references for research on other basic tastes.